Comparative Study based on Horizontal and Vertical Networks for Monitoring Certain Structures Case study: Two Dams in the Southern Region of Syria (Daraa and Taffass) (Damascus University Journal for engineering sciences, 2021)
Due to the great importance of hydrological facilities (like dams) after construction is finished and put into service. There is an urgent need for reliable and continuous monitoring by geodetic means. This study aimed to establish a robust geodetic reference framework (horizontal and vertical) that enables engineers continuously monitor horizontal and vertical displacements. In order to achieve efficiency and safety measures, certain aspects has to be proposed to identify best surveying arrangements and devices to reach the required accuracy. The study was performed collecting data from two important dams in the southern region of Syria (Daraa Dam and Taffass Dam) in Daraa province. At the end, the research proposed a separate study for each Dam was carried out in which ntwoks were established taking into consideration the structural and engineering characteristics of that Dam. Appropriate solutions and methodology for best geodetic configuration as well as the necessary instrumentation that should be used to achieve the required accuracy for each case. Namely the scientific work follows two methodologies:-1st method: statistically, using mathematical modeling for fitting the data (measurements)-2nd method: practically, periodical or systematic measurements (data) were collected at various stages.
Keywords: Deformation monitoring; Horizontal displacements; Vertical displacements